Clinical picture and treatment of myasthenia gravis in the adult population - Swatko, Tomasz; Marzeda, Magdalena; Blicharz, Agnieszka; Małek, Anna; Sygacz, Oliwer (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Myasthenia gravis (MG, myasthenia gravis ) is a classic example of an autoimmune disease caused by antibodies against acetylcholine receptors ( AChR) , muscle-specific kinase (MuSK) or other AChR-related proteins in the postsynaptic muscle membrane leading to characteristic muscle weakness. Description of the state of knowledge: It is not fully known why the body begins to produce antibodies that act against its own acetylcholine receptors. The main role in producing these antibodies is played by the thymus gland, a gland located in the chest. The thymus gland is normally present in children, while it atrophies in adults. In about 60% of myasthenia gravis patients, however, it is present (we say they have a persistent thymus), and 15% of patients have a thymic neoplasm called a thymoma. Summary: Myasthenia gravis is the most common neuromuscular junction disorder. Myasthenia gravis is a rare disease that involves muscle weakness of the eyes, pharynx, larynx, respiratory muscles and limbs. Clinical manifestations vary depending on the type of autoantibody and the presence of thymoma. The diagnosis of the disease should be confirmed by electrodiagnostic and laboratory tests in addition to the typical symptoms. Myasthenia gravis can manifest at any age, both in men ( peak incidence 50-60 years of age) and women ( peak incidence 20-30 years of age). Muscle fatigue intensifies after any exercise, even small ones. The patient feels best in the morning hours, right after waking up. As time passes, the symptoms of muscle fatigue intensify and the patient becomes less and less fit. For this reason, patients should rest frequently.